Passionate Amateurs Theatre, Communism and Love - Ridout, Nicholas (University of Michigan Press, 2013)
Beginning with Chekhov's Uncle Vanya, Passionate Amateurs tells a new story about modern theater: the story of a romantic attachment to theater's potential to produce surprising experiences of human community. Ridout argues that theater in modern capitalism can help us think afresh about notions of work, time, and freedom. Passionate Amateurs tells a new story about modern theater: the story of a romantic attachment to theater's potential to produce surprising experiences of human community. It begins with one of the first great plays of modern European theater-Chekhov's Uncle Vanya in Moscow-and then crosses the 20th and 21st centuries to look at how its story plays out in Weimar Republic Berlin, in the Paris of the 1960s, and in a spectrum of contemporary performance in Europe and the United States.